Economia și societatea sub lentila multiculturalismului. Contraste: heterocromie și heterocronie economico-socială: Economy and society under the lens of multiculturalism. Contrasts: Heterochromy and economic-social heterochrony - Bodea, Gabriela (Swedish Journal of Romanian Studies, 2024)
Multiculturalism implies social acceptance: it does not involve consensus, but social awareness. As witnesses of diversity, we identify change itself, as a continuous process, relativised by aspects of heterochromy and socioeconomic heterochrony. The dichotomy of differentiated development does not follow a particular pattern. Simultaneously, it seems dual: it seduces through a certain degree of freedom (discernible, perceptible, or apparent), but it also makes itself guilty through the reticence that singles it out. In the end, differentiation brings advantages and requires sacrifices, but it is as much a part of the spirit of the individual as it is of the way economic entities act.